Abdominal investigations in the year preceding a diagnosis of abdominal cancer: A register-based cohort study in Denmark. (June 2021) - Jessen, Nanna Holt; Jensen, Henry; Falborg, Alina Zalounina; Glerup, Henning; Gronbaek, Henning; Vedsted, Peter
Highlights: Several types of investigations are performed across different abdominal cancers. The investigations are performed with varying frequency in the year before diagnosis. Increased use is seen for all investigations; the onset differs between cancer types. Increased use is primarily seen in the 2–6 months before the diagnosis. Some of the performed investigations are typically used to detect other cancers. Abstract: Background: More than 11, 500 abdominal cancers are yearly diagnosed in Denmark. Nevertheless, little is known about which investigations the patients undergo before a diagnosis of abdominal cancer. We aimed to investigate the frequency and timing of selected diagnostic investigations during the year preceding an abdominal cancer diagnosis. Methods: We conducted a nationwide registry-based cohort study of patients aged ≥ 18 years who were diagnosed with a first-time abdominal cancer in 2014−2018. We included the following cancer types: oesophageal, gastric, colon, rectal, liver, gall bladder/biliary tract, pancreatic, endometrial, ovarian, kidney, and bladder cancer. Investigations of interest were transvaginal ultrasound, abdominal ultrasound, colonoscopy, gastroscopy, endoscopic retrograde cholangiopancreatography, cystoscopy, hysteroscopy, abdominal computed tomography and abdominal magnetic resonance imaging. Generalised linear models were used to calculate incidence rate ratios to enable comparison of monthly rates of investigations. Results: All types of investigations were performed, with varying frequency, across the 11 abdominal cancer types in the year preceding the diagnosis. Increased use of investigations revealed that the timing of the onset differed for the different abdominal cancers, with increases seen 2–6 months before the diagnosis. Abdominal ultrasound, colonoscopy and computed tomography were the investigations with the earliest increase. Conclusion: In the year before a diagnosis of an abdominal cancer, some patients appear to undergo investigations typically used to detect another cancer type. This indicates that a window of opportunity exists to diagnose some abdominal cancers at an earlier time point. Future studies should explore an alternative clinical pathway to promote earlier diagnosis of abdominal cancers.